PEMBERIAN MOBILISASI ROLL SLIDE TERHADAP DAN MANUAL TRAKSI INTENSITAS SKALA NYERI LUTUT PADA PENDERITA OSTEOARTHRITIS DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Isidorus Jehaman; Rini Hardiyanti; Sabirin Berampu; Raynald Ignasius Ginting; Redi Tantangan (JURNAL PENGMAS KESTRA (JPK), 2021)
Osteoarthritis is a chronic joint disease characterized by abnormalities in the cartilage (cartilage) of the joints and nearby bones. Cartilage is part of the layer that lines the ends of bones, to facilitate movement of the joints. The occurrence of osteoarthritis is influenced by various risk factors such as age (aging process), genetics, obesity, joint injury, anatomical abnormalities, metabolic diseases and joint inflammatory diseases. This activity aims to determine the effect of providing Roll Slide Mobilization and Manual Traction on knee scale intensity in patients with Osteoarthritis. The method used to treat problematic patients is Roll Slide Mobilization and Manual Traction with the number of interventions being 22 samples. The measuring instrument used for evaluation uses the VAS scale. The results of the interventions that have been carried out show that there is an effect of Roll Slide Mobilization and Manual Traction Interventions on the intensity of knee pain in Osteoarthritis patients reaching 91%. Suggestions Researchers suggest that this method can then be applied as a method that can be chosen to overcome knee problems.